Teachers and Partners are Involved in implementation Project Based Learning Model of Biology Education at SMAN 13 Medan - Yustiningsih, Nurul; Hasibuan, Virda Kartika; Putri, Auliani; Simanullang, Nadia; Simatupang, Halim; Arwita, Widya (Pusdikra Publishing, 2024)
This research was carried out at the State High School 13 Medan. The population of this study was 32 pupils and 2 biology teachers. The evaluation methods used in this research are quantitative methods and library studies. Education is a conscious and planned effort to create a good learning atmosphere and produce good students anyway. The Merdeka Curriculum is a curriculum with diverse intra-curricular learning where content is more optimal so that students have enough time to deepen concepts and strengthen skills. One of the schools that implemented the Merdeka curriculum is the SMAN 13 Medan. Results found from observations of problems or shortcomings in the PjBL learning model are available in time, cost, and LKPD.